The impact of the Pillar One and Pillar Two proposals on MNE's investment costs An analysis using forward-looking effective tax rates - Hanappi, Tibor (OECD Taxation Working Papers, 2020)
This working paper presents the analytical framework used by the Secretariat to estimate the direct effects of the Pillar One and Pillar Two proposals on MNE's investment costs. The analysis builds on the standard ETR framework and extends it in two important respects. First, ETRs are calculated for an investment performed by an entity belonging to an MNE group and account for the possibility that MNEs use their organisational structure to shift profits to low tax jurisdictions. Second, the model incorporates a stylised version of the tax provisions introduced under Pillar One and Pillar Two. The results, covering over 70 jurisdictions, account for differences in tax bases and rates, and are empirically calibrated to map MNE activities, i.e., the location of their profits, turnover and assets as well as the impact of the proposals. Overall, the results suggest that the Pillar One and Pillar Two proposals would lead to modest increases on global weighted ETRs. This paper feeds into the broader analysis of the investment impacts of the Pillar One and Pillar Two proposals